Environmental scan of mental health supports across Canadian burn centers: A healthcare providers' perspective. Issue 3 (May 2023) - Padalko, Adam; Bergeron, Nicolas; Cristall, Nora; Peter Gawaziuk, Justin; Logsetty, Sarvesh
Abstract: Background: Early mental health care and psychosocial support after burn injury provided by a variety of specialists and non-mental health professionals is instrumental in prevention of long-term mental health sequalae such as post-traumatic stress, depressive or substance use disorders. Diversity of mental health supports available to burn survivors vary across geography, resulting in variation of long-term mental health outcomes following burn injury. Methods: A mixed-methods study utilizing a semi-structured questionnaire to explore resources available for burn survivors in Canada as an inpatient, outpatient, and more broadly in the aftercare community. Interviews were completed with 17 Canadian burn centers, with a variety of burn care professionals. Results: In the continuum of burn care, a lack of available mental health professionals in certain regions and in the outpatient and community phases was observed. Emerging themes demonstrated the need for regular screening for mental health concerns among burn survivors and providing up to date discharge resources. In addition, increasing educational opportunities available to burn care staff with respect to burn survivor mental health was emphasized. Lastly, the importance of proactive and prolonged psychological support for burn survivors as they progress through an outpatient, rehabilitation and community setting was underlined. Conclusions: Identification of burn care practices and resources across Canada provides the opportunity to compare, unify and improve gaps in care that exist across the Canadian burn network. Highlights: Increased mental health support for burn survivors is needed in Canada. A diversity in supports for burn survivors contributes to variation in outcomes. Consistent burn team education on mental health complexities needed. A lack of mental health screening post-burn injury was identified.